Analisis Pengawasan dan Pengaduan Masyarakat Terkait Lingkungan di bidang PPKLH Dinas Lingkungan Hidup dan Kebersihan Sidoarjo - Anugrah Dewanta, Raven; Nurvita Cundaningsih (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Environmental monitoring and complaint systems are essential components in the protection and management of the environment. This study aims to analyze the effectiveness of monitoring mechanisms and community-based complaint systems regarding environmental violations in Indonesia. A qualitative method with a descriptive-analytical approach was employed through literature review, regulatory analysis, and case studies in several areas of Sidoarjo. Based on the analysis of community complaints data from 2024 and 2025, industrial activities continue to pose serious environmental problems. In 2024, manufacturing industries dominated the complaints, primarily related to air and water pollution, ineffective waste management, and inadequate equipment usage. These issues directly affected nearby communities, causing noise and pollution that reached residential areas. Meanwhile, in 2025, small and medium-sized enterprises (SMEs) were identified as the main contributors to pollution due to the lack or suboptimal operation of wastewater treatment plants (WWTP) and air emission filters. Insufficient public outreach and knowledge regarding waste management also led to indiscriminate waste disposal into surrounding waterways. Overall, the most common violations by both industry types were related to air and water pollution regulations.